2020
DOI: 10.1002/jlb.5mr0320-200r
|View full text |Cite
|
Sign up to set email alerts
|

Immune system and cholangiocytes: A puzzling affair in primary biliary cholangitis

Abstract: Primary biliary cholangitis (PBC) is a cholestatic liver disease characterized by the destruction of the small and medium bile ducts. Its pathogenesis is still unknown. Despite the genome wide association study findings, the therapies targeting the cytokines pathway, tested so far, have failed. The concept of the biliary epithelium as a key player of the PBC pathogenesis has emerged over the last few years. It is now well accepted that the biliary epithelial cells (BECs) actively participate to the genesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 194 publications
(352 reference statements)
3
18
0
Order By: Relevance
“…5 d and Additional file 2 : Table S10). These results are consistent with previous evidence that an immune-mediated injury of cholangiocytes contributes risk to PBC [ 30 , 31 ].
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…5 d and Additional file 2 : Table S10). These results are consistent with previous evidence that an immune-mediated injury of cholangiocytes contributes risk to PBC [ 30 , 31 ].
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…We found that cholangiocytes showed a notable enrichment by PBC-relevant genetic association signals (Permuted P < 0.05, Figure 3b and Supplemental Table S10). These results are consistent with previous evidence that an immune-mediated injury of cholangiocytes contributes risk to PBC 44,45 .…”
Section: Resultssupporting
confidence: 93%
“…We found that cholangiocytes showed a notable enrichment by PBC-relevant genetic association signals (Permuted P < 0.05, Figure 5d and Supplemental Table S10). These results are consistent with previous evidence that an immune-mediated injury of cholangiocytes contributes risk to PBC [30,31].…”
Section: Identification Of Genetically-influenced Liver Cell Subpopulations For Pbcsupporting
confidence: 93%